Periodic Points of Asymmetric Bernoulli Shifts - Yong-Guo Shi; Kai Chen; Wei Liao (Journal of Mathematics)
It is well-known that Sharkovskii’s theorem gives a complete structure of periodic order for a continuous self-map on a closed bounded interval. As a further study, a natural problem is how to determine the location and number of periodic points for a specific map. This paper considers the periodic points of asymmetric Bernoulli shift, which is a piecewise linear chaotic map.